Clear Lensectomy with Hydrus Stent in Black and Afro-Latino Patients: A 1-Year Retrospective Study - Daniel Laroche; Jessinta Oseni; Gideon Nkrumah; Chester Ng (Journal of Ophthalmology)
Purpose. To determine the efficacy and safety of phacoemulsification, clear lensectomy, and the Hydrus microstent (Ivantis, Inc.) in Black and Afro-Latino glaucoma patients. Method. This is a retrospective nonrandomized study of 134 Black and Afro-Latino patients who underwent clear lensectomy with Hydrus stent implant for the treatment of glaucoma. For comprehensive analysis, patients were divided into mild, moderate, and advanced glaucoma. The evaluated parameters were reductions in the number of medications, intraocular pressure (IOP), mean deviation on visual field test, and visual acuity. Results. A total of 134 patients with 1-year follow-up were evaluated. At 1 year, the average number of medications significantly decreased from 2.5 ± 1.4 preoperatively to 0.43 ± 1.04 (p<0.001) and IOP decreased from 14.4 ± 3.9 to 13.8 ± 3.10 (p=0.16). 110 (82.1%) patients were medication-free at 1 year (n = 57, 83.8% mild glaucoma; n = 37, 92.5% moderate glaucoma; n = 16, 61.5% advanced glaucoma). There was stabilization of mean deviation on the visual field test (baseline, −8.28; 1 year, −8.28; p=1). The most reported adverse effects were transient IOP spike and hyphema (n = 7, 5.2%; n = 3, 2.2%, respectively); both events were self-resolving. No decline in vision or sight-threatening complications were reported at 1 year, and no additional surgeries were required. Conclusion. This 1-year retrospective study demonstrated the efficacy and safety of clear lensectomy and Hydrus stent implantation in decreasing medication burden while maintaining lower IOP in Black and Afro-Latino glaucoma patients.